Forecasting National People's Salt Production with Time Series Model Using POM-QM for Windows - Badi'ah, Roudlotul; Odelia, Evi Maya; Effendi, Rusfian (Jurnal Ilmiah Poli Bisnis, 2022)
The need for salt in Indonesia continues to increase yearly, but the performance of salt production in Indonesia has not been able to meet the targets set in the 2015-2019 KKP strategic plan. This study aims to properly obtain time series forecasting methods and estimates of the amount of national salt production in 2022 to find out Indonesia’s needs of salt. The data are the 2012-2021 Directorate General KP3K/PRL performance report, 2012-2021 KKP performance and annual reports, and the 2020-2024 KKP strategic plan. Forecasting analysis techniques use naive methods, moving averages, weighted moving averages, exponential smoothing, exponential smoothing with trend, and trend analysis using POM-QM for Windows 3. The results show that the selected forecasting method predicts the amount of national salt productions are trend analysis with total production in 2022 of 1,277,392 tons because it has the smallest MAD, MSE, and MAPE forecasting errors compared to other methods, so that the results of this forecasting can be used for policy design in the future.